EFEKTIFITAS EKSEKUSI PERADILAN TATA USAHA NEGARA BERDASARKAN UNDANG-UNDANG NOMOR 51 TAHUN 2009 - Soeleman Baranyanan (Faculty of Law, Universitas Pattimura, 2017)
The enforcement of justice and the limitation of the use of violence are two of the many conditions and values or the upholding of democracy. One of the institutions for the implementation of democratic values is the existence of a free judicial system to guarantee human rights and to maintain justice. The urgency of the existence of administrative justice in realizing the rule of law encourages the government to establish a legal system in the administrative court. Namely through the establishment of Act No. 5 of 1986 on the State Administrative Court, which is the foundation for the establishment of the State Administrative Court in Indonesia. In the explanation of Law Number 5 Year 1986 mentioned that the State Administrative Court was held in order to provide protection to the people of the court of justice, who felt themselves harmed by a Decision of State Administration. In principle, a country is expected to provide protection to the human rights of its citizens. What is done through the separation or distribution of state power, because the centralization of state power absolutely in one hand alone makes authoritarian government. While the government based on the law is expected to guarantee the protection of the human rights of its citizens.